A Review on Potential Role of Silver Nanoparticles and Possible Mechanisms of their Actions on Bacteria - Khalandi, Bahar; Asadi, Nahideh; Milani, Morteza; Davaran, Soodabeh; Abadi, Azam Jafari Najaf; Abasi, Elham; Akbarzadeh, Abolfazl (Drug Research, 2017)
The antimicrobial property of silver is associated to the quantity of silver and the grade of silver released. The ionized silver is extremely sensitive, as it binds to tissue proteins and gets operational alterations in the bacterial cell wall and nuclear membrane leading to cell modification and death.Silver nanoparticles have the talent to anchor to the bacterial cell wall and consequently infiltrate it, so causing physical modifications in the cell membrane like the absorptivity of the cell membrane and death of the cell. There are numerous concepts on the act of silver nanoparticle on bacteria to reason the microbicidal influence.
Keywords: antimicrobial property; silver nanoparticle; nuclear membrane; bacterial cell